1982
DOI: 10.1073/pnas.79.4.1210
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the vaccinia virus thymidine kinase gene by marker rescue and by cell-free translation of selected mRNA

Abstract: (8,9) or DNA recombinants (10, 11). However, the task of assigning these polypeptides to specific functions has just begun. Indeed, until now, no poxvirus proteins with known functions have been mapped by molecular or classical genetic methods.Early mRNAs of vaccinia virus that have been examined in detail do not appear to be spliced or shortened at their 5' ends (12-15). For one early mRNA, the nucleotides within the 60-bp sequence immediately upstream ofthe initiation site are 89% adenylate and thymidylate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
113
1

Year Published

1982
1982
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(116 citation statements)
references
References 34 publications
2
113
1
Order By: Relevance
“…This observation contrasts the previously reported requirement of carrier DNA for optimal marker rescue in another poxvirus, vaccinia (27,28). The difference is likely not due to differential uptake into the cells, because CaPO4 precipitates enter the cytoplasm of cells with great efficiency, even in the absence of DNA (29).…”
Section: Discussioncontrasting
confidence: 56%
“…This observation contrasts the previously reported requirement of carrier DNA for optimal marker rescue in another poxvirus, vaccinia (27,28). The difference is likely not due to differential uptake into the cells, because CaPO4 precipitates enter the cytoplasm of cells with great efficiency, even in the absence of DNA (29).…”
Section: Discussioncontrasting
confidence: 56%
“…At the other extreme of viral complexity, Sam and Dumbell (1981) and Weir, Bajszar and Moss (1982) have reported marker rescue of mutants of vaccinia virus with genomie fragments of vaccinia viral DNA. Weir and colleagues showed that methotrexate-resistant TK+ (thymidine kinase) vaccinia virus was formed in cells coinfeeted with TK~ virus and wild-type (i.e.…”
Section: Construction Of Hybrid Virusesmentioning
confidence: 99%
“…All of the HindlII fragments, except HindIII-J, were alternatively introduced with tk or aprt in order to determine if different vectors could influence the biological properties of the transformants. Since the HindIII-J fragment contains the vaccinia virus tk gene (Hruby & Ball, 1982;Weir et al, 1982), this fragment was introduced into recipient cells using G418 selection because this marker is not involved in nucleic acid metabolism.…”
Section: (Accepted 21 March 1984)mentioning
confidence: 99%